International Outsourcing, the Nature of Tasks, and Occupational Stability – Empirical Evidence for Germany - Daniel Baumgarten (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
Using a large administrative data set of individual employment histories in Germany, this paper studies how international outsourcing affects the individual risk of leaving the occupation. Moreover, a rich data set on tasks performed in occupations is used to better characterize the sources of worker vulnerability. While international service outsourcing is associated with an increase in overall stability, the impact of international material outsourcing is slightly negative. These effects, however, are not uniform but depend on the nature of tasks performed in the occupation. Higher intensities of non-routine and interactive tasks are associated with a more beneficial (or less adverse) impact of international outsourcing on occupational stability.
Keywords: F16; J23; J24; J63; 330; Occupational stability; international outsourcing; duration analysis; Arbeitsplatzsicherung; Anforderungsprofil; Outsourcing; International; Offshoring; Branche; Beschäftigungseffekt; Deutschland